EARLY (AVANT-GARDE) SYMPHONIES BY VALENTIN SILVESTROV AS A SOUND UNIVERSE - Liudmyla SHAPOVALOVA; Іryna ROMANIUK; Marianna CHERNYAVSKA; Svitlana SHCHELKANOVA (Studia Universitatis Babeş-Bolyai. Musica, 2021)
In the article under consideration are the ways of symphony genre transformation in the early works of Valentin Silvestrov (Ukraine). For the first time, the First, Second, Third, and Fourth symphonies by the genius composers of the 20th century are analyzed as a certain stylistic system. These compositions are endowed with the features of avant-garde poetics, and as a subject of musicological reflection, they are associated with a rethinking of the semantic paradigm of the genre. V. Silvestrov's early symphonies stand out from the classical practice of European symphonies. Scientific awareness of their phenomenal nature necessitated a methodological choice aimed at the most accurate identification of the philosophical concept of the new sound universum of V. Silvestrov's music. Deep correlation of the image of a human being as a factor of the symphony poetics (the influence of philosophical concepts of human ontology in the 20th century with the transformation of the genre canon) is considered. This refers to the nonmusical dimension of the genre semantics. The study of V. Silvestrov's early symphonies reveal a new philosophy of music through gradual movement – modulation: from the neo-baroque First Symphony and "cosmic pastorals" Musica Mundana of the Second Symphony through the history anthropologisation in the Third Symphony "Eschatology" to the monodrama Musica Humana in the Fourth Symphony. The dichotomy of Musica Mundana – Musica Humana is not accidental: in V. Silvestrov's creative method, remains relevant, which is confirmed by the dramaturgy of his latest work – the Ninth symphony (2019).